A NEW MODEL OF PROFESSIONAL EDUCATION AS AN IMPERATIVE OF KNOWLEDGE-BASED ECONOMY - Sergey A. Filatov; Natalya G. Sukhorukova; Tatiyana N. Dudina (Высшее образование в России)
This article analyzes the objective factors that cause the need for the new model of professional education in the conditions of the formation of knowledge-based economy. The socio-economic mechanism of transformation of the educational system in the post-industrial era is revealed. The experience of the university is presented.